THE RELATIONSHIP BETWEEN SERVICE QUALITY AND PATIENT SATISFACTION IN THE PRIMARY CLINIC OF THE DIRECTORATE GENERAL OF REGIONAL DEVELOPMENT, MINISTRY OF HOME AFFAIRS - Sukma Waty, Dwi (Rifapublisher.id, 2025)
Background: Service activities at healthcare facilities are closely linked to service quality, facilities, and patient satisfaction. Consumer satisfaction is the feeling of pleasure or disappointment that arises after comparing their perception or impression of a product's performance or outcome with their expectations. Patient satisfaction is related to the service quality of healthcare facilities. By knowing the level of patient satisfaction, management can improve service quality. Objective: To determine the relationship between healthcare service quality and patient satisfaction at the Primary Clinic of the Directorate General of Regional Development, Ministry of Home Affairs. Methods: This research is a quantitative analytical study with a cross-sectional design. The sample formula used in this study is the Slovin formula, with a total of 94 respondents selected using accidental sampling technique. Bivariate data analysis was performed using the chi-square test. Results: The univariate results showed good service quality at 95.7% and poor quality at 4.3%, while patient satisfaction was 94.7% satisfied, 3.2% fairly satisfied, and 2.1% dissatisfied. Bivariate analysis found a significant influence between service quality and patient satisfaction at the Primary Clinic of the Directorate General of Regional Development, Ministry of Home Affairs, with a P-value of 0.001. Conclusion: Good service quality will increase the level of patient satisfaction as service recipients.